Estudo do comportamento termodinâmico da pimenta-longa durante o processo de adsorção de umidade - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1999)
The aromatic plants group of the Botany Department of MPEG studied the long pepper (Piper hispidinervium C.DC.), a species rich in essential oil containing safrole (80-97%), and established a production system based on its cultivation technology and its field processing (drying and distillation), allowing the generation of about 1,000 oil/ha/year. These data were obtained based on a drying process with maintenance of a moisture content between 20-30%, followed by steam distillation, with a yield of only 50%. The drying process is fundamental in the processing of the plant, considering that the essential oil of the long pepper, for being denser than water, emulsifies easily, making the process of separation of the phases very laborious and, consequently, of low yield. The present work was designed to analyze the kinetics of water adsorption by long pepper, at different temperatures and relative humidities; to construct moisture adsorption isotherms based on the GAB (Guggenheimer-Anderson-de Boer) model and; to determine their isosteric adsorption heats. The static gravimetric approximation method used showed high accuracy to describe the adsorption isotherms. The long pepper showed low adsorption heats in the range of moisture content, which was expected since there is little variation in equilibrium moisture contents at the different temperatures considered. The GAB equation fitted very well to the experimental points obtained in the moisture adsorption process of long pepper. The experimental data obtained will serve to model the design of prototype field dryers that will be tested in the processing of the plant.
Study of the thermodynamic behavior of long pepper during the process of moisture adsorption
Keywords: Piper hispidinervium c.dc; Plantas aromáticas; Óleo essencial; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA